INHEEMSE ERFOPVOLGINGSREG IN ZIMBABWE: LESSE VIR SUIDAFRIKA DEEL I: ERFOPVOLGINGSREG VOOR HERVORMING - Elmarie Knoetze (Obiter, 2022)
The article, consisting of two parts, considers the reform of the customary law of succession in Zimbabwe, with a view to extract lessons for the South African legislature. In the first part of the article the relevant law in Zimbabwe before the statutory reform of 1997 is considered, with reference to conflicting case law impacting on the rights of an African female to inherit.